How do eating disorders can affect the endocrine system? - literature review - Iwan, Karolina; Bielak, Alicja; Gryta, Jakub; Janczewska, Martyna; Kalicka, Maria; Kolasa, Agata; Krysa, Tomasz; Radziejowska, Zuzanna; Szklarz, Magdalena (Journal of Education, Health and Sport, 2023)
Introduction: Eating disorders (ED) are complex psychological disorders with low rates of detection and early intervention. High rates of morbidity and mortality in eating disorders, especially anorexia nervosa (AN), is still continued. ED mostly refers to adolescent and lead to many significant complications, including many changes in endocrine system. Hormonal disorders in AN occur among sex hormones, thyroid hormones, adrenal hormones, growth hormones, as well as the entire hypothalamic-pituitary axis. Purpose of the study: The aim of this study is to collect and summarize the latest views on endocrine dysregulation in anorexia nervosa and highlights the complications associated with it. Material and method: Literature review was performed in English different databases, using keywords: eating disorders, anorexia nervosa, menstruation, menses, irregular menstruation, estrogen, bone mineral density, cortisol, hipercortisolemia, insulin, leptin, ghrelin, growth hormone, thyroid, tyrosine. Results and conclusions: In our systematic review we would like to present the most significant hormone dysregulation in anorexia nervosa and how they can affect the whole organism, such as gonadal axis disregulation, menstrual disorders, bone mineral density, hipercortisolemia, hypoglycemia and other that anorexia nervosa may cause. The phenomenon of eating disorder is becoming more and more frequent – for this reason it is important to put attention to that and be aware of many complication ED can lead to, including hormonal changes.